2020
DOI: 10.1097/scs.0000000000006098
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Intraarticular Injection Substances Followed by Temporomandibular Joint Arthroscopy

Abstract: Nowadays, temporomandibular joint (TMJ) arthroscopies are often finished with intraarticular injections. There are a couple of different substances that can be injected into the articular cavity following arthroscopy; however, it is still unclear which one can help to reach the best clinical results. The aim of this systematic review was to compare different substances that can be injected intraarticularly following TMJ arthroscopy to enhance clinical success. A review protocol was regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Only Xie et al 28 reported no effects of HA injections on functional outcomes; on the contrary, improvements in MMO have been reported by nine articles. 29,30,[35][36][37][38]41,43,45 When compared to placebo, treatments including HA showed better results: data obtained by Al-Moraissi et al 39…”
Section: Effects On Functionmentioning
confidence: 90%
See 4 more Smart Citations
“…Only Xie et al 28 reported no effects of HA injections on functional outcomes; on the contrary, improvements in MMO have been reported by nine articles. 29,30,[35][36][37][38]41,43,45 When compared to placebo, treatments including HA showed better results: data obtained by Al-Moraissi et al 39…”
Section: Effects On Functionmentioning
confidence: 90%
“…Publication date of the included studies ranged between 2010 and 2022, and interesting to note, 13 systematic reviews or meta-analyses were published in the last 5 years. Thirteen studies [28][29][30][33][34][35][36][37][38][39][40][41][42] included only randomized controlled clinical trials (RCTs) and eight systematic reviews 28,34,36,38,39,[43][44][45] also performed a meta-analysis on the data of the included studies. All articles but one 44 performed a systematic search on at least two databases.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations